CLINICAL PHARMACOLOGY IN ADAPTIVE REGULATION OF STRESS PATHWAYS IN MEGACOLON INTENSIVE CARE - Shеrova Z. N.; Yakubjanov M. O. (Journal Park Publishing, 2025)
Analysis and optimization of anesthetic management and intensive care during intra-abdominal resection in children with Hirschsprung disease to improve treatment efficacy and reduce postoperative risks. Materials and Methods: The study examined the performance of 65 children (aged 3 to 14 years) who underwent elective abdominal surgery (abdominoperineal proctoplasty) with various modifications: gastroentero-entero anastomoses, entero-entero anastomoses, and intestinal ulcer resections with various signs of perioperative pain. In the operating room of the Tashkent Pediatric Medical Institute from 2021 to 2024. Results: After premedication, a comparative analysis of heart rate assessments at baseline revealed no significant differences between the two clinical comparison groups (p>0.05). During the run-in period, a significant decrease in heart rate was recorded: 15.2% in Group 2 compared to Group 1 (p<0.05). During the maintenance period, heart rate decreased by 9% in both groups. A non-significant increase was recorded during the awakening period, by 10% (p<0.005), and by 8.3% in Group 1. Extubation was performed early after surgery, with a statistically significant 11.9% higher prevalence in Group 2 than in Group 1. Children with Hirschsprung disease (congenital aganglionosis) often experience severe postoperative complications, such as enterocolitis, sepsis, abdominal compartment syndrome, and multiple organ dysfunction. These conditions are associated with excessive activation of the stress response, necessitating the development of new approaches to its control. [1, 3]. Stress-limiting mechanisms (antioxidant, anti-inflammatory, and neuroprotective) play a key role in adaptation to surgical trauma. Their targeted stimulation (e.g., through pharmacological agents or neuromodulation) can accelerate recovery and reduce the risk of complications. [5, 6, 8] This minimum of adverse effects is achieved through the use of low doses of administered drugs. This technique provides better early results in surgical correction of intra-abdominal resections in abdominal surgery and fewer complications [2, 4, 7].